Effectiveness and cost of multilayered colorectal cancer screening promotion interventions at federally qualified health centers in Washington State. Issue 21 (25th October 2018) - Kemper, Kathryn E.; Glaze, Becky L.; Eastman, Casey L.; Waldron, Roxane C.; Hoover, Sonja; Flagg, T'Ronda; Tangka, Florence K. L.; Subramanian, Sujha
Abstract: Background: It has been demonstrated that fecal immunochemical test (FIT) mailing programs are effective for increasing colorectal cancer (CRC) screening. The objectives of the current study were to assess the magnitude of uptake that could be achieved with a mailed FIT program in a federally qualified health center and whether such a program can be implemented at a reasonable cost to support sustainability. Methods: The Washington State Department of Health's partner HealthPoint implemented a direct‐mail FIT program at 9 medical clinics, along with a follow‐up reminder letter and automated telephone calls to those not up‐to‐date with recommended screening. Supplemental outreach events at selected medical clinics and a 50th birthday card screening reminder program also were implemented. The authors collected and analyzed process, effectiveness, and cost measures and conducted a systematic assessment of the short‐term cost effectiveness of the interventions. Results: Overall, 5178 FIT kits were mailed with 4009 follow‐up reminder letters, and 8454 automated reminder telephone calls were made over 12 months. In total, 1607 FIT kits were returned within 3 months of the end of the implementation period: an overall return rate of 31% for the mailed FIT program. The average total intervention cost per FIT kit returned was $39.81, and the intervention implementation cost per kit returned was $18.76. Conclusions: The mailed FIT intervention improved CRC screening uptake among HealthPoint's patient population. This intervention was implemented for less than $40 per individual successfully screened. The findings and lessons learned can assist other clinics that serve disadvantaged populations to increase their CRC screening adherence. Abstract : The Washington State Department of Health, through their partner HealthPoint, implements multiple interventions, including the mailed fecal immunochemical test. The combination of interventions reaches patients who rarely or never are screened for colorectal cancer, reducing barriers to screening and ultimately improving colorectal cancer screening uptake among HealthPoint's patient population.